How We Talk about the Movies: A Comparison of Australian, British and American Film Genre Terms. Issue 3 (2nd July 2020) - White, Hollie; Hider, Philip
ABSTRACT: Vocabulary or terminological control has been an issue of critical information practice for Australian information professionals for many years. In the 1970s Australian libraries began to supplement Library of Congress Subject Headings with their own List of Australian Subject Headings, and today there remains the bibliographic need to cover uniquely Australian terms and concepts, including those about Indigenous Australian culture. The library world is not the only domain, however, to have developed vocabularies to describe and make sense of information resources. Comparison of film genre vocabularies is of particular interest because film studies have often assumed a fixed set of categories, regardless of geography, culture or time. Although much of today's film industry is 'global', with a strong Hollywood influence on genre to sell movies, this does not mean that filmmakers, nor film audiences, use a set vocabulary. This paper looks at whether similar geographical biases may be discerned in vocabularies used in the domain of film curation by examining the variation in terminology and the classification of film genres used by film institutes based in Australia, the United Kingdom and the United States.